The Geographic Structure оf The Synanthropic Flora оf Biloozersky National Nature Park (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The results of geographic study by Meusel (Meusel, Jager, Weinert, 1965; Meusel, Jager, 1992) of the synanthropic flora of Biloozersky National Nature park showed that the temperate-submedional species (43,7 %) are prevail in latitudinal spectrum of chorological groups. It is typical for flat temperate latitudinal floras of Holarctic region. The species of Euroasian group, which have Europe and circumpolar area are distributed in temperate area boreal zones and predominante in spectrum of regional chorological groups of flora. Cosmopolite species are minor in studied flora. The species of Euryoceanic and indisferent groups are predominante by oceaniccontinentality. In general correlation between oceanic and continental climat types of areas confirms intermediate character of flora of park. Thus, the division of areal groups of flora is evidens of its forest-steppes character of Middle European floras.
Keywords: Biloozersky National Park, synanthropic flora, georaphic structure, species, area.